Apat dapat, dapat apat - Deramas, Wenn.; Del Rosario, Mel Mendoza; Tamayo, Arlene; Quinto, Rufa Mae.; Domingo, Eugene; Pokwang; Pangilinan, Candy; Viva Films (Pasig City Viva Films, 2007)
From the creative team of Ang Cute ng Ina Mo comes another rib-tickling comedy about a friendship that never ends. Brite owns a funeral parlor, Dolly is a struggling piano teacher, Gay is a separated MMDA and Res is a full-time housewife living with her two kids and perpetually lazy husband, Totoy Bato. The four meet under strange circumstances and vow to become friends for life...and death! Their lives take a turn for the worse when Brite suggests they work abroad to earn more money. The three of them agree except for Res who keeps thinking something bad might happen to them. But perhaps it is their fate to stick together. In Hong Kong, the friends land different jobs but manage to meet often until one fateful day when Res doesn't show up. The friends discover that Res was killed by her employers and afraid that Totoy Bato would kill them if he finds out about Res' Fate they decide to bring her home alive at all costs! Its one unforgetable laugh trip after another as the friends try to get away with their modus operandi.
DVD
Story by Mel Mendoza-Del Rosario, screenplay by Mel Mendoza-Del Rosario and Arlene Tamayo, producers Vicente Del Rosario III and Veronique Del Rosario-Corpus, executive producers Rufa Mae Quionto & Vic Del Rosario, Jr.
Rufa Mae Quinto, Eugene Domingo, Pokwang, Candy Pangilinan.
Keywords: Comedy films; Feature films